2021
DOI: 10.3390/ani11020573
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Proteomics Analysis of In Vitro Canine Oviductal Cell-Derived Extracellular Vesicles

Abstract: Dogs (Canis lupus familiaris) have unique and peculiar reproductive characteristics. While the interplay between in vitro oviductal cell-derived extracellular vesicles (OC-EVs) and cumulus-oocyte complexes in dogs has begun to be elucidated, no study has yet provided extensive information on the biological content and physiological function of OC-EVs and their role in canine oocyte development. Here, we aimed to provide the first comprehensive proteomic analysis of OC-EVs. We identified 398 proteins as present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
3
6
0
Order By: Relevance
“…EVs act as cell‐to‐cell communication nanoparticles (Mathieu et al, 2019) containing micro RNA and small RNA molecules that mediate cell signaling and epigenetics (Park et al, 2019; Saadeldin et al, 2014; Spadafora, 2020). Results showed the expression of SOD1 in the OEC EVs that supports the evidence that oviductal secretion provide antioxidative defense to the early embryos (Lee et al, 2021; Li & Winuthayanon, 2017). The oviduct is a vital organ for early embryonic development due to the secretion of epithelial cells (Kölle et al, 2020; Lee et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…EVs act as cell‐to‐cell communication nanoparticles (Mathieu et al, 2019) containing micro RNA and small RNA molecules that mediate cell signaling and epigenetics (Park et al, 2019; Saadeldin et al, 2014; Spadafora, 2020). Results showed the expression of SOD1 in the OEC EVs that supports the evidence that oviductal secretion provide antioxidative defense to the early embryos (Lee et al, 2021; Li & Winuthayanon, 2017). The oviduct is a vital organ for early embryonic development due to the secretion of epithelial cells (Kölle et al, 2020; Lee et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…Oviduct epithelial cells (OESs) secrete oviductal fluid (OF) and play important roles in reproductive events, participating in final gamete maturation, fertilization, and early embryonic development (González‐Brusi et al, 2020; Tukur et al, 2020). Moreover, the OF mediates an early embryo‐maternal dialog through cell‐to‐cell contacts, secreted molecules, and extracellular vesicles (EVs) (Lee et al, 2021; Saint‐Dizier, Schoen, Chen, Banliat, & Mermillod, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, melatonin has been identified in OF‐derived EVs from rabbits (Qu, Luo, et al, 2020). Furthermore, a recent study revealed that several proteins associated with rough ER functions, such as endoplasmin (HSP90), 40S ribosomal protein S26, and 60S ribosomal protein L13a, were also detected in in vitro canine oviductal cell‐derived EVs, as determined by liquid chromatography‐tandem mass spectrometry (Lee et al, 2021). In line with the above evidence, we propose that porcine oviductal EVs may relieve ER stress in preimplantation embryos via the bioactive molecules contained in them.…”
Section: Discussionmentioning
confidence: 99%
“…EVs, including exosomes and microvesicles, are membrane-enveloped particles secreted by living cells to the surrounding microenvironment and body fluids, and contain proteins, messenger RNA (mRNA), and microRNAcargoes. In different mammalian species, EVs have been detected in all reproductive biofluids with emerging evidence on their roles in gametogenesis, fertilization, early embryo development, and implantation (2)(3)(4)(5)(6).…”
Section: Editorial On the Research Topic Biofluid Extracellular Vesicles And Their Involvement In Animal Reproductive Physiologymentioning
confidence: 99%